MORE HUMAN THAN HUMAN: POSTHUMANISM IN LITERARY DISCOURSE - Gumanay, Jorisse Campado (Sanata Dharma University, 2023)
“What makes us human?” Throughout time, people have been preoccupied with this question, believing that humans are at the pinnacle of the world. Today, technology blurs the boundaries of what is considered “natural” versus “enhanced,” leading to a fallout with the limited views of humanism and modernity. This paper explores the many views on posthumanism that have been established by several thinkers to attempt to understand the concept. An illustrative text is then used to elucidate the implication of the posthumanist thought in literature. Posthumanist themes are prevalent in science fiction, embodying people’s collective anxiety toward the looming future of humanity, such as in the works of Philip K. Dick. The story “The Electric Ant” poses existential questions on the nature of reality and our place in it, with highly posthumanist themes such as the presence or assimilation of robots in human societies. Posthumanism is as yet a complex and broad field of study, challenging our notions of what it means to be human and alive, and making us ask questions about how the present and future of technology could shape our human existence.